Manipulating the solubility properties of polymer donors for high-performance layer-by-layer processed organic solar cells. Issue 11 (22nd September 2021) - Ning, Haijun; Jiang, Qiuju; Han, Pengwei; Lin, Man; Zhang, Gongya; Chen, Jinming; Chen, Hui; Zeng, Shuyi; Gao, Jinping; Liu, Jiangang; He, Feng; Wu, Qinghe
Abstract : This study demonstrates that the solubility properties of polymer donors are vitally important for layer-by-layer processed organic solar cells. Manipulating the solubility of an NTI-based polymer donor enables 17.59% efficiency for a PNTB6-Cl:N3 based device. Abstract : High-performance polymer donors are highly demanded to fulfil the potential of layer-by-layer (LBL) processed organic solar cells (OSCs). In this study, we present an effective method to develop high-performance polymer donors for LBL-OSCs by manipulating their solubility properties. The solubility of naphthalenothiophene imide (NTI)-based polymers could be easily manipulated by employing linear or branched alkyl chains in NTI. The polymer PNTB6-Cl with linear alkyl chains insoluble in chloroform could tolerate the chloroform processing by washing away the polymers only in the amorphous region, resulting in an LBL film with a much smoother surface and more efficient photoluminescence quenching, while chloroform-soluble polymer PNTB-Cl did not. PNTB6-Cl:N3 based LBL devices exhibited an efficiency of 17.59%, much higher than 15.24% for PNTB-Cl:N3 based devices and 16.20% for control devices based on PM6:N3. Importantly, the excellent batch-to-batch reproducibility of PNTB6-Cl overcomes the notorious batch-dependent issue in polymer donors, indicating that PNTB6-Cl is a promising polymer donor for LBL-OSCs. Our studies demonstrate that the solubility property of a polymer could significantly impact electron acceptor penetration, phase separation and photovoltaic performance of LBL-OSCs, which provide the guidelines for high-performance polymer donor design.